Phytochrome A and phytochrome B mediate the hypocotyl-specific downregulation of TUB1 by light in arabidopsis. - Leu, W M (1995)
Arabidopsis contains six alpha-tubulin and nine beta-tubulin genes that are expressed in a tissue-specific and developmentally regulated manner. We analyzed the effects of light on tubulin mRNA abundance in Arabidopsis seedlings using RNA gel blot hybridizations and gene-specific probes. Transcript levels of all 15 tubulin genes were decreased by continuous white light, although to different degrees. Detailed analysis was performed with the beta-tubulin TUB1 gene. The transcript level of TUB1 was high in etiolated seedlings and decreased to approximately 20% of the dark mRNA level after 2 to 6 hr of white light treatment. We showed that this downregulation requires high-irradiance light treatment and that multiple photoreceptors are involved. In particular, using phytochrome mutants and narrow wave band light, we demonstrated that both the phytochrome A (phyA)-mediated far-red light high-irradiance response and the phytochrome B (phyB)-mediated red light high-irradiance response are involved in the downregulation of TUB1 expression by white light. Histochemical analysis of transgenic plants expressing a TUB1-beta-glucuronidase chimeric transgene indicated that the downregulation observed only in hypocotyls and not in roots is controlled transcriptionally.